Optimal Tariffs and Firm Technology Choice: An Environmental Approach - Nico Steffen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper introduces the additional dimension of environmental concerns by a government into a setting of rent-extracting strategic trade policy with endogenous firm investment into production technologies. It considers the presence of imperfect competition, namely Cournot competition. The simple analysis highlights the importance of investment incentives caused by tariffs. Furthermore, the implications from traditional tariff considerations can be completely different to the ones derived with an environmentally conscious government. It is shown that an importing country now prefers to impose discriminatory instead of uniform tariffs in a dynamic setting with endogenous technology choices, in order to induce the exporting firms to choose a technology that exhibits lower costs in terms of emissions.
Keywords: F18; F13; Q58; 330